A descriptive analysis of vales and Maqasid al-Shari'ah in social media use among students of IIUM - Shompa, Zohora Azmin; Saidin, Aznan Zuhid; Hussin, Husnayati; Muhammad, Muhd. Rosydi; Abu Bakar, Elistina (IIUM Journal Publication Unit, 2019)
The use of social media has raised concern on users’ ability to behave ethically in cyberspace. Handling various issues in social media lies in the person of using social media properly from the Islamic perspectives. This study consists of a descriptive analysis of responses from 250 respondents among students of International Islamic University Malaysia. Description is given regarding the values and social media use from the perspective of Maqasid al- Shari‘ah which are to protect religion, life, intellect, privacy, reputation, and property. The Pearson correlation shows a significant relationship between values and social media use. This study plays an important role in shaping the behavior in social media use based on the six essentials above that will create awareness, promote safe and responsible use of social media.